Conceptualising predictors of attitudes toward and revisit intentions to a winescape - Thomas, Ben (School of Marketing, Curtin Business School, 2010)
This paper aims to conceptualise the commonly referred to "winescape" in wine tourism literature and develop a scale to measure its effects on wine tourist attitudes and revisit intentions to a wine region. Integrating theoretical underpinnings from services and tourism marketing into existing wine tourism literature a framework for the proposed winescape is presented incorporating the theory of planned behaviour. The proposed winescape construct contains wine region destination attributes, signage and layout and service staff, while the remaining constructs within the study include wine tourist motivation, attitude towards the winescape, subjective norms, perceived behavioural control, revisit intentions and past experience with the winescape. Involvement will be used as a background construct to segment the sample and will have a proposed moderating effect on the model. Other relationships within the model and the contributions of the study will also be examined.